SOCIALIZATION OF IMPROVING THE QUALITY OF HEALTH ADMINISTRATION SERVICES THROUGH THE USE OF DIGITAL TECHNOLOGY - Hamdana, Erika; Johan, Herni (LPPM Univ. Ibn Khaldun Bogor, 2025)
The rapid development of digital technology has influenced the management of health services, particularly in financial administration at primary health centers. This study focuses on Segiri Public Health Center Samarinda, which still relies heavily on manual processes in managing the Health Operational Assistance (BOK) fund. Field observations revealed challenges such as delays in reporting, limited human resources, weak coordination, and inadequate use of information technology, all of which hinder service quality. Problem identification using a Fishbone Diagram indicated that the main issue lies in the suboptimal use of digital systems influenced by human, financial, procedural, and infrastructural factors. Alternative solutions were analyzed using the Reinke Method, with the development of a digital application integrated with Google Workspace identified as the top priority, supported by hybrid SOPs, staff training, archive digitization, and budget optimization. The internship findings conclude that strengthening digital-based financial administration is essential to improve efficiency, accountability, and reporting quality, thereby supporting better health services for the community.